Advances in malaria vaccine development: report from the 2017 malaria vaccine symposium. (December 2017) - Coelho, Camila; Doritchamou, Justin; Zaidi, Irfan; Duffy, Patrick
Abstract The Malaria Vaccine Symposium occurred at Johns Hopkins University in Baltimore, MD, USA on April 25th, 2017, coinciding with World Malaria Day and the WHO announcement that the RTS, S malaria vaccine would begin pilot implementation programs in Ghana, Kenya, and Malawi in 2018. Scientists from several disciplines reported progress on an array of malaria vaccine concepts and product candidates, including pre-erythrocytic vaccines that prevent infection, blood-stage vaccines that limit infection and disease, and transmission-blocking vaccines that interrupt the spread of infection. Other speakers highlighted the immunological and genetic considerations that must be addressed by vaccinologists to yield the most efficacious vaccines. Here, we highlight the advances in malaria vaccinology that were reported at the symposium.